Age of rogues rebels, revolutionaries and racketeers at the frontiers of empires - Öztan, Ramazan Hakkı; Yenen, Alp 1982- (Edinburgh University Press, 2022)
Studies the frontier cultures of revolution that shaped the making of the modern Middle EastUses a novel conceptual framework that charts the rise of transgressive politics in the frontiers of empiresIncludes a variety of biographical approaches to the key disruptive figures during the crisis of imperial and post-imperial regimes in the regionRepresents a connected geography of imperial collapse and nation-state formation in 12 case study chaptersEngages with scholarship on intercommunal violence, revolutionary politics, and subaltern agencyIn Age of Rogues, leading scholars engage with themes of historical and cultural legacies, contentious interactions within imperial regimes, and the biographical trajectory of men and women who challenged the political status quo of their time.Rebels, revolutionaries and racketeers played central roles in the violent process of imperial disintegration as it unfolded in the frontiers of the Ottoman, Habsburg, Romanov and Qajar empires. This is a history of these transgressive actors from the late-19th century to the interwar years. This time was marked by similar, if not shared, revolutionary experiences and repertoires of contention across the connected geography of the Balkans, the Middle East and the Caucasus
Keywords: Geschichte 1870-2020; Islamic Studies; HISTORY / Europe / General; Imperialism -- History -- 20th century; Revolutionaries -- History -- 20th century; Politik; Rebell; Gauner; Imperialismus; Revolutionär; Naher Osten; Balkan; Kaukasus; Aufsatzsammlung